2017
DOI: 10.3847/1538-4357/aa69bc
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Value Theory and the New Sunspot Number Series

Abstract: Extreme value theory was employed to study solar activity using the new sunspot number index. The block maxima approach was used at yearly (1700–2015), monthly (1749–2016), and daily (1818–2016) scales, selecting the maximum sunspot number value for each solar cycle, and the peaks-over-threshold (POT) technique was used after a declustering process only for the daily data. Both techniques led to negative values for the shape parameters. This implies that the extreme sunspot number value distribution has an upp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 47 publications
2
18
0
Order By: Relevance
“…Moreover, the return levels are reaching a plateau, and it will be unlikely that the sunspot numbers will attain values greater than the already observed ones in the future. This generally agrees with a similar analysis carried out using the sunspot number based in telescopic data for the last four centuries (Acero et al 2017). …”
Section: Discussionsupporting
confidence: 91%
“…Moreover, the return levels are reaching a plateau, and it will be unlikely that the sunspot numbers will attain values greater than the already observed ones in the future. This generally agrees with a similar analysis carried out using the sunspot number based in telescopic data for the last four centuries (Acero et al 2017). …”
Section: Discussionsupporting
confidence: 91%
“…However, it should be pointed out that the extreme value theory can be used to study the solar extreme events. For example, Acero et al (2017Acero et al ( , 2018Acero et al ( , 2019 employed this technique to study the temporal variability of the sunspot number and the solar radio flux, and found that there is an upper bound for the distribution of the peak values of the photospheric and coronal indicators. Therefore, the coronal magnetic activity exhibits the similar kind of behavior as the sunspot activity, implying that the features that cause the coronal modulation are rooted in surface magnetic structures.…”
Section: Comparison With the Sunspot Number Datamentioning
confidence: 99%
“…For this purpose, we use a set of statistical techniques commonly called extreme value theory (EVT). These techniques are beginning to be used to better characterize the extreme values of different indices related to space storms (Acero et al, 2017(Acero et al, , 2018Elvidge & Angling, 2018).…”
Section: Introductionmentioning
confidence: 99%